The effectiveness of micro financial (Ar-Rahn) towards empowering the small muslim entrepreneur in Kelantan / Muhamad Sahidan Adnan - Adnan, Muhamad Sahidan (2013)
This research paper title is “The effectiveness of micro financial (ar- rahn) towards empowering the small muslim entrepreneur in Kelantan”. The researcher intended to identify the factors that influence the effectiveness of micro financial (ar- rahn) towards empowering the small muslim entrepreneur. Therefore the researcher has proposed two independent variables that might influence the respondent’s intention namely source of capital and encourage investment. Further detailed of the variables is discussed in Chapter 2. On Chapter 1 of the report, the researcher includes information regarding the background of the study, the objective of the study and etc. The population for this research is people who use Ar rahnu for business at Kota Bahru and the researcher decided to take 100 of the peoples as the research sample, further detailed on the research methodology was discuss in Chapter 3. In order to achieve the research objective, the researcher had conduct five analysis which are frequency analysis, descriptive analysis, reliability analysis, hypothesis testing (correlation analysis) and multiple regression. The entire analysis finding is present in Chapter 4. The last chapter which is Chapter 5 discuss regarding conclusion and recommendations from the researcher.